2004
DOI: 10.1177/070674370404900607
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Psychological Impact on SARS Patients during the Outbreak

Abstract: General stress and negative psychological effects are increased in SARS patients, particularly among infected health care workers. This may increase the risk of mood and stress-related disorders. Functional impairment is apparent in the postrecovery phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
160
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 8 publications
14
160
0
9
Order By: Relevance
“…8,12,13 These results revealed that the risk of direct or indirect exposure to SARS would bring a greater psychological impact from SARS. Social support from others, taking precautionary measures, and clear disease information has been reported as protective factors for the exposed patient or health workers.…”
mentioning
confidence: 81%
“…8,12,13 These results revealed that the risk of direct or indirect exposure to SARS would bring a greater psychological impact from SARS. Social support from others, taking precautionary measures, and clear disease information has been reported as protective factors for the exposed patient or health workers.…”
mentioning
confidence: 81%
“…[479][480][481][482] Patients placed under Transmission Precautions may experience increased anxiety, depression, loneliness, and stress as well as anger and hostility. 483,484 Compared with control patients, adult patients isolated for MRSA were more likely to have preventable adverse events (eg, falls, ulcers, or fluid and electrolyte abnormalities), to complain about their care, to have fewer vital signs taken, and to have more days without physician progress notes.…”
Section: Studies Among Non-cf Patientsmentioning
confidence: 99%
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress [150] and mood disturbances [151]. Furthermore, steroid toxicity, personal vulnerability and psychosocial stressors might have contributed to the development of psychosis in some patients [152].…”
Section: Long-term Outcomementioning
confidence: 99%